2017
DOI: 10.1016/j.healun.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor patterns and right heart failure in mechanical circulatory support

Abstract: Background Right Ventricular failure (RVF) complicates 9–44% of LVAD implants postoperatively. Current prediction scores perform only modestly in validation studies, and do not include immune markers. Chemokines are inflammatory signaling molecules with a fundamental role in cardiac physiology and stress adaptation. We aimed to study chemokine receptor regulation in LVAD recipients who develop RVF. Methods Expression of chemokine receptor genes 3–8 was examined in the peripheral blood of 111 LVAD patients, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Overall, the role of cytokine-signaling in the post-LVAD pathophysiology is evidently associated with the events that determine adverse ventricular remodeling, as seen by Grosman-Rimon et al’s report ( 29 ), who demonstrate recipients with continuous-flow LVADs as demonstrating a higher level of inflammatory biomarkers and specific expression changes in the chemokine signaling pathway. Contrastingly, Nayak et al ( 30 ) found increased mortality was associated with the downregulation of chemokine signaling, and these effects were translated by the progression toward right heart failure—one of the fatal complications of LVAD assistance. Disparities maybe due to the different types of devices, or the lengths of time the LVAD assistance remained in place, but the validation of this requires further study and investigation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, the role of cytokine-signaling in the post-LVAD pathophysiology is evidently associated with the events that determine adverse ventricular remodeling, as seen by Grosman-Rimon et al’s report ( 29 ), who demonstrate recipients with continuous-flow LVADs as demonstrating a higher level of inflammatory biomarkers and specific expression changes in the chemokine signaling pathway. Contrastingly, Nayak et al ( 30 ) found increased mortality was associated with the downregulation of chemokine signaling, and these effects were translated by the progression toward right heart failure—one of the fatal complications of LVAD assistance. Disparities maybe due to the different types of devices, or the lengths of time the LVAD assistance remained in place, but the validation of this requires further study and investigation.…”
Section: Discussionmentioning
confidence: 93%
“…CX3CR is involved in chemokine binding. Nayak et al found that when chemokine signaling was downregulated, it increased mortality and facilitated the fatal adverse effects after LVAD implantation, particularly, the process of right heart failure ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that chemokine dysregulation potentiates the progression of end‐stage HF . Nayak et al found that downregulation of chemokine signaling increased mortality and facilitated the process of right heart failure, which is one of the fatal adverse effects after LVAD implantation. However, in Grosman et al’s report, a higher level of inflammatory biomarkers and specific expression changes in the chemokine signaling pathway were observed in the recipients with continuous‐flow LVADs.…”
Section: Discussionmentioning
confidence: 99%
“…Readily available inflammatory markers such as white cell count, neutrophil to lymphocyte ratio, or C reactive protein correlate with rates of RVF ( 62 ). A more in-depth analysis showed that patients with RVF displayed a pre-operative downregulation of chemokine receptors CCR3, 4, 6, 7, and 8 that was even more profound in patients who required RVAD, which suggests a dose-response relationship that supports a causative role ( 63 ). Other inflammatory biomarkers such as procalcitonin, neopterin, or endothelin 1 have also been linked to RVF ( 64 ).…”
Section: Pre-operative Prediction Of Right Ventricular Failurementioning
confidence: 99%